Search for angiotensin II receptor antagonists among 4-aryl-n-(aryl)-3-(prop-2-en-1-yl)-2,3-dihydro-1,3-thiazol-2-imine derivatives - Iryna Drapak; Borys Zimenkovsky; Lina Perekhoda; Мargarita Suleyman; Hanna Yeromina; Natalia Skaletska; Natalya Seredynska; Anatoly Demchenko (Pensoft Publishers, 2019)
The aim of study was to find potential antihypertensive and cardiotropic drugs among new 4-aryl-N-(aryl)-3-(prop-2-en-1-yl)-2,3-dihydro-1,3-thiazol-2-imines. Materials and methods: The target compounds were synthesized by condensation asymmetrical substituted thioureas with α-bromo-4-R1-acetophenones in ethanol medium. The structure and purity of the compounds synthesized were confirmed by 1H, 13C NMR-spectroscopy and elemental analysis. Docking studies of synthesized compounds to the active site of angiotensin receptor ІІ (PDB ID: 3R8A) were performed in order to find its potential inhibitors and to select promising compounds for experimental screening. Pharmacological studies of the influence on the cardiovascular system were performed. Results: The results of docking studies indicate a high affinity of all tested substances to the selected biotarget. The thermodynamic probability of binding of synthesized substances to protein 3R8A was confirmed by negative values of scoring functions. Hydrobromide of 4-(4-methoxyphenyl)-N-phenyl-3-(prop-2-en-1-yl)-2,3-dihydro-1,3-thiazol-2-imine 3(1) and hydrobrmide of 4-(4-methoxyphenyl)-N-(4-bromphenyl)-3-(prop-2-en-1-yl)-2,3-dihydro-1,3-thiazol-2-imine 3(3), which have the highest negative values of scoring functions, are recommended for in vivo pharmacological studies. Based on a complete analysis of the geometric location of the synthesized compounds (ligands) in the active site of the angiotensin II receptor, it was found that the complexes are formed with the involvement of Nitrogen atom of imino group, the 1,3-thiazole ring, the phenyl and alkyl moieties of the molecule form hydrogen bonds, intermolecular electrostatic and donor-acceptor interactions. The conducted pharmacological studies of the influence on the cardiovascular system have allowed to confirm the presence of antihypertensive effect inherent in compounds of this series (except for compound 3(2)). The most effective antihypertensive effect, which is similar in duration and strength of the effect of valsartan, was the effect of compound 3(5). Conclusions: In order to expand the arsenal of biologically active substances of cardiotropic action a systematic series of new 4-aryl-N-(aryl)-3-(prop-2-en-1-yl)-2,3-dihydro-1,3-thiazol-2-imine derivatives were synthesized. The structure and purity of the compounds synthesized were confirmed by 1H, 13C NMR-spectroscopy and elemental analysis. Based on the results of docking studies using Autodock 4.2.6 software, selected compounds with the best affinity for protein biomes (PDB codes: 3R8A) are promising for experimental studies of hypotensive and cardiotropic activity. The most effective antihypertensive effect, which is similar in duration and strength of the effect of valsartan, was the effect of compound 3(5). A comparative analysis of the results of molecular docking and in vivo results suggests that there is a positive correlation between scoring protein inhibition and experimental data.